The Influence of Leadership, Competence and Motivation on the Performance of Congregational Financial Management at Port Numbay Klassis - Christian, Ferdinandus; Numberi, Tresya I; Monim, Melkias; Krey, Abraham; Lolowang, Nancy Lidya (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study aims to analyze the influence of leadership, motivation, and competence on the performance of congregation financial management at the GKI Port Numbay Klassis. This study employed a quantitative approach with an explanatory design to investigate the impact of leadership, competence, and motivation on the performance of congregation financial managers in Klasis Port Numbay. Data were collected through surveys and interviews with 98 financial managers across 49 congregations, with cluster sampling used to represent the population. The analysis included validity, reliability, and classical assumption tests, followed by multiple regression analysis to determine each independent variable's influence on performance, individually and collectively. The research found that leadership, competence, and motivation play crucial roles in enhancing the performance of financial managers in the congregation at Klasis GKI Port Numbay. Effective leadership provides clear direction and motivation, leading to improved performance. High competence in skills, knowledge, and work attitude significantly contributes to the managers' ability to perform their tasks optimally. Additionally, strong motivation among financial managers is key to achieving set performance targets. Leadership, competence, and motivation significantly influence the performance of financial managers, highlighting their importance in ensuring efficient and effective financial management in a church setting.